THE PLAYFULNESS AS PROMOTER OF HUMAN DEVELOPMENT IN THE EDUCATION OF YOUNG CHILDREN (Fiep Bulletin - online, 2011)
This research took as its object of study the playfulness, considered by the Sociology of Childhood, as one of the axis of the Cultures of Childhood. Assumed that Pre-School Education institutions have a secondary this activity to its resume. It was established as a central objective: to investigate how the cultures of childhood are understood in the Childhood Education context and how they were worked the axis playfulness. The methodology is qualitative, it was characterized as action-research and was developed in two rooms of the Pre II in an Kindergarten Municipal Institution in Presidente Prudente city, for twelve months. As for results, we highlight in the foreground, the methodology itself, whose citizens participation of the partner institution, the university team performance in the context investigated, and the pursuit of transformation of reality demands increased commitment, mutual respect, team work and tolerance among the actors. The studies, the debates led discussions between concepts and indicated different looks for the child and for educational practice. The two teachers expanded their vision, especially on children's participation in recreational activities, because they charged behaviors too strict, that turned into obstacles to the freedom, movement, imagination and fun. This understanding has led educators to realize, also, the need for their role as mediators and co-responsible for a practice in Childhood Education that ensures the necessary resources for the development of different languages, of which playfulness is a special resource that contributes to the improvement of educational quality in this teaching method.
Keywords: Childhood Education; Cultures of Childhood; Playfulness